Isokinetic knee strength deficit in patients with moderate haemophilia. Issue 4 (17th February 2021) - Fouasson‐Chailloux, Alban; Maugars, Yves; Trossaert, Marc; Rannou, François; Menu, Pierre; Vinatier, Claire; Guicheux, Jérôme; Dauty, Marc
Abstract: Introduction: Knee joint bleedings are responsible for quadriceps atrophy and strength deficit in patients with severe haemophilia. Little is known about patients with moderate haemophilia (PWMH). Aim: To evaluate isokinetic quadriceps and hamstrings strength in PWMH and to assess correlation with radiological and clinical parameter. Methods: 18 PWMH aged 37.1 ± 11.4 and 18 healthy age‐, weight‐ and height‐matched controls performed a knee isokinetic test at 180°/s to assess quadriceps and hamstrings strength. In the PWMH group, knee Pettersson's score was pursued and Haemophilia Joint Health Score 2.1 (HJHS) was performed to determine unaffected knees (knee HJHS = 0) and affected ones (knee HJHS >0). Results: Affected knees had a decrease of quadriceps strength compared to controls, 1.26 ± 0.47 vs 1.64 ± 0.27 Nm/kg and a decrease of hamstring strength, 0.60 ± 0.29 vs 1.03 ± 0.21 Nm/kg, ( P < 0.001). Unaffected knees also had a decrease of quadriceps strength compared to controls, 1.36 ± 0.31 vs 1.64 ± 0.27 Nm/kg and a decrease of hamstring strength, 0.69 ± 0.18 vs 1.03 ± 0.21 Nm/kg, ( P < 0.001). The conventional hamstring‐to‐quadriceps ratio was significantly decreased in affected knees compared to controls, 0.46 ± 0.15 vs 0.64 ± 0.13 ( P < 0.001) but also in unaffected knees, 0.53 ± 0.16 vs 0.64 ± 0.13 ( P = 0.02).No correlation was found between strength and HJHS or Pettersson's score. Conclusion: PWMH have a significant knee strength deficit, both on the quadriceps and the hamstrings, which is responsible for an important muscle imbalance.